Robotic Level IV Inferior Vena Cava Thrombectomy Using an Intrapericardial Control Technique: Is It Safe Without Cardiopulmonary Bypass?. Issue 1 (4th January 2023) - Huang, Qingbo; Zhao, Guodong; Chen, Yonghui; Wu, Peng; Li, Shuanglei; Peng, Cheng; Liu, Kan; Yu, Hongkai; Gao, Yubo; Xiao, Cangsong; Fu, Qiang; Shen, Hao; et al.
Abstract : Purpose: We introduce an intrapericardial control technique using a robotic approach in the surgical treatment of renal tumor with level IV inferior vena cava thrombus to decrease the severe complications associated with cardiopulmonary bypass and deep hypothermic circulatory arrest. Materials and Methods: Eight patients with level IV inferior vena cava thrombi not extending into the atrium underwent transabdominal-transdiaphragmatic robot-assisted inferior vena cava thrombectomy obviating cardiopulmonary bypass/deep hypothermic circulatory arrest (cardiopulmonary bypass-free group) by an expert team comprising urological, hepatobiliary, and cardiovascular surgeons. The central diaphragm tendon and pericardium were transabdominally dissected until the intrapericardial inferior vena cava were exposed and looped proximal to the cranial end of the thrombi under intraoperative ultrasound guidance. As controls, 14 patients who underwent robot-assisted inferior vena cava thrombectomy with cardiopulmonary bypass (cardiopulmonary bypass group) and 25 patients who underwent open thrombectomy with cardiopulmonary bypass/deep hypothermic circulatory arrest (cardiopulmonary bypass/deep hypothermic circulatory arrest group) were included. Clinicopathological, operative, and survival outcomes were retrospectively analyzed. Results: Eight robot-assisted inferior vena cava thrombectomies were successfully performed without cardiopulmonary bypass, with 1 open conversion. The median operation time and first porta hepatis occlusion time were shorter, and estimated blood loss was lower in the cardiopulmonary bypass-free group as compared to the cardiopulmonary bypass group (540 vs 586.5 minutes, 16.5 vs 38.5. minutes, and 2, 050 vs 3, 500 mL, respectively). Severe complications (level IV-V) were also lower in the cardiopulmonary bypass-free group than in cardiopulmonary bypass and cardiopulmonary bypass/deep hypothermic circulatory arrest groups (25% vs 50% vs 40%). Oncologic outcomes were comparable among the 3 groups in short-term follow-up. Conclusions: Pure transabdominal-transdiaphragmatic robot-assisted inferior vena cava thrombectomy without cardiopulmonary bypass/deep hypothermic circulatory arrest represents as an alternative minimally invasive approach for selected level IV inferior vena cava thrombi.